Quality and Implementation of Social Science Printed Modular Distance Learning in Public Senior High Schools - Rosales, Kaye Anne; Legaspi Jr., Carlos Eduardo (Technium Social Sciences Journal, 2022)
Given the adverse effects that the pandemic would have on learning and education in general, educational institutions were forced to switch to a new format where distance learning became necessary for learners and educators worldwide. In the Philippines, the Department of Education (DepEd) responded by providing comprehensive and inclusive distance learning modules for continuous learning. Thus, this descriptive study determined the level of quality and extent of implementation of Printed Modular Distance Learning (PMDL) as assessed by the social science teachers when grouped according to educational attainment, grade level taught, and schools division. Through a survey instrument, this study was administered to 105 social science senior high school teachers in the selected schools divisions of northern Negros Occidental. In analyzing the data, descriptive analysis was employed. The general findings of the study unveiled that both the quality and implementation of PMDL excellently adhere to the national standards set by the Department of Education. This signifies that teachers and stakeholders properly implemented and actively participated in the Printed Modular Distance Learning. Findings suggest a comprehensive continuity plan to support teachers in continuing the high quality and implementation of PMDL in public senior high schools.